2019
DOI: 10.1002/cctc.201900611
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Immobilization in MOF‐derived Porous NiO with Hierarchical Structure: An Efficient and Stable Enzymatic Reactor

Abstract: MOF‐derived porous NiO with hierarchical structure (MHNiO) was prepared based on thermolysis of Ni metal organic framework (Ni‐MOF), which was used as carrier for the immobilization of horseradish peroxidase (HRP) and cytochrome C (Cyt c). The pore size of MHNiO was tuned as 11.8 nm to match the size of free enzyme so as to depress the aggregation of the enzymes in the pore. Meanwhile, the hierarchical structure allowed the substrates concentrated in the vicinity of the enzymes. The obtained enzymatic reactors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 58 publications
0
14
0
2
Order By: Relevance
“…The hydrogel with an egg-box network structure is triggered by Ca 2+ produced by the reaction of CH 3 COOH with CaCO 3 in the sol solution. As the alginate network grows, enzymes GO x (6.0 nm × 5.5 nm × 7.7 nm) and HRP (4.4 nm × 4.4 nm × 6.8 nm) and TMB are encapsulated. The hydrodynamic diameter of tens of nanometers was estimated for TMB since 3,3′-diaminobenzidine (DAB), which has a similar structure to that of TMB, was estimated to have a hydrodynamic radius of tens of nanometers .…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogel with an egg-box network structure is triggered by Ca 2+ produced by the reaction of CH 3 COOH with CaCO 3 in the sol solution. As the alginate network grows, enzymes GO x (6.0 nm × 5.5 nm × 7.7 nm) and HRP (4.4 nm × 4.4 nm × 6.8 nm) and TMB are encapsulated. The hydrodynamic diameter of tens of nanometers was estimated for TMB since 3,3′-diaminobenzidine (DAB), which has a similar structure to that of TMB, was estimated to have a hydrodynamic radius of tens of nanometers .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the separation of the catalyst from the product, a time‐consuming and costly process, is substantially accelerated for MOF‐embedded enzymes [6, 21] . Several proof‐of‐principle studies have demonstrated the potential MOF‐hosted enzymes, but so far studies were mostly limited to simple batch experiments [22–24] . Continuous‐flow experiments as required for technologically relevant applications have not yet been reported for enzymes infiltrated in MOF systems.…”
Section: Methodsmentioning
confidence: 99%
“…[6,21] Several proof-of-principle studies have demonstrated the potential MOF-hosted enzymes, but so far studies were mostly limited to simple batch experiments. [22][23][24] Continuous-flow experiments as required for technologically relevant applications have not yet been reported for enzymes infiltrated in MOF systems. Tian et al reported a continuous flow reactor filled with MOF coated micelles containing the enzyme CALB.…”
mentioning
confidence: 99%
“…Darüber hinaus wird die Trennung des Katalysators vom Produkt – ein zeit‐ und kostenaufwendiger Prozess – bei in MOF eingebetteten Enzymen erheblich beschleunigt [6, 21] . Mehrere Proof‐of‐Principle‐Studien haben das Potenzial von in MOF eingebetteten Enzymen aufgezeigt, bislang waren die Studien jedoch meist auf einfache Batch‐Experimente beschränkt [22–24] . Experimente mit einem kontinuierlichen Durchfluss, wie sie für technologisch relevante…”
Section: Methodsunclassified